2021
DOI: 10.3389/fonc.2021.639874
|View full text |Cite
|
Sign up to set email alerts
|

A Four-Gene-Based Prognostic Model Predicts Overall Survival in Patients With Cutaneous Melanoma

Abstract: BackgroundCutaneous melanoma (CM) is one of the most aggressive cancers with highly metastatic ability. To make things worse, there are limited effective therapies to treat advanced CM. Our study aimed to investigate new biomarkers for CM prognosis and establish a novel risk score system in CM.MethodsGene expression data of CM from Gene Expression Omnibus (GEO) datasets were downloaded and analyzed to identify differentially expressed genes (DEGs). The overlapped DEGs were then verified for prognosis analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…The macrophages and B cells express PU.1, which is required for myeloid cell differentiation ( Klemsz et al, 1990 ; Valledor et al, 1998 ). As reported by ( Tong et al, 2021 ), high ADAMDEC1 expression was significantly correlated with better prognosis. MARCO was also identified as one of six diagnostic and prognostic biomarkers for patients with lung adenocarcinoma ( Shang et al, 2017 ).…”
Section: Discussionsupporting
confidence: 66%
“…The macrophages and B cells express PU.1, which is required for myeloid cell differentiation ( Klemsz et al, 1990 ; Valledor et al, 1998 ). As reported by ( Tong et al, 2021 ), high ADAMDEC1 expression was significantly correlated with better prognosis. MARCO was also identified as one of six diagnostic and prognostic biomarkers for patients with lung adenocarcinoma ( Shang et al, 2017 ).…”
Section: Discussionsupporting
confidence: 66%
“…This antitumor activity of recombinant GRNLY was also demonstrated in vivo, initially by intratumoral injection in several tumors types: mammary carcinoma, multiple myeloma and melanoma [15,16]. There are abundant data that relate granulysin expression to an active antitumor immune response and to a good prognosis [31][32][33][34]. Although mice do not express a granulysin homologue, the Alan Krensky group generated transgenic mice that expressed human granulysin and showed an increased resistance to tumor development [35].…”
Section: Discussionmentioning
confidence: 97%
“…Just recently, survival prognosis in melanoma was correlated with immune-related gene signatures (70)(71)(72). Of note, Danaher et al (73) found that TIS was also highly statistically significantly prognostic in TCGA-SKCM, limiting its predictive value in melanoma patients.…”
Section: Discussionmentioning
confidence: 99%